Instrumental and affective influences on public trust and police legitimacy in Spain - Bradford, Ben (2016)
Two approaches to the nature and sources of public trust and police legitimacy can be distinguished: the instrumental and the affective. On the rst account, people trust in police when they judge it effective in enforcing the law and ghting crime; and they hold police more legitimate when they believe these things to be true. On the second account, trust and legitimacy are bound up with relational concerns about the quality of police behavior, and expressive factors relating to the perceived ability of communities and police to maintain and reproduce social cohesion and order. Studies in Anglophone contexts tend to conclude that this 'affective' account provides greater explanatory power. This paper explores these ideas in a new context. Using data from a nation- wide survey conducted in Spain we examine: (a) the relative strength of instrumental or affective predictors of trust; and (b) whether trust in police fairness is a more or less important predictor of legitimacy than trust in police effectiveness. Adding to the weight of international evidence concerning the ways people think about and experience policing, evidence for the primacy of the affective account is presented